A Novel lncRNA HOXC-AS3 Acts as a miR-3922-5p Sponge to Promote Breast Cancer Metastasis. (2nd January 2020) - Shi, Sheng-Hong; Jiang, Jing; Zhang, Wei; Sun, Long; Li, Xu-Jun; Li, Chao; Ge, Qi-Dong; Zhuang, Zhi-Gang
Abstract: Purpose: The function of long noncoding RNAs (lncRNA) in breast cancer metastasis remains largely unknown. In this work, the role of HOXC-AS3 in breast cancer progression was investigated. Methods: By using Cancer Genome Atlas (TCGA) Database, we investigated the expression of HOXC-AS3 in breast cancer and explored the association between HOXC-AS3 expression and prognosis. Then, we studied the biological function of HOXC-AS3 in cell migration and invasion both in vitro and in vivo . Furthermore, the target miRNA of HOXC-AS3, and the target mRNA of miR-3922-5p were proved. Results: HOXC-AS3 is aberrantly overexpressed in breast cancers especially the HER2 + type. Moreover, high expression of HOXC-AS3 has a relationship with poor clinical outcomes of breast cancer. In addition, HOXC-AS3 regulates cell Invasion and migration both in vitro and in vivo . Our results demonstrated that miR-3922-5p was a direct target of HOXC-AS3, and PPP1R1A was a target of miR-3922-5p in breast cancer. Conclusions: The novel lncRNA HOXC-AS3 acts as a miR-3922-5p sponge to upregulate PPP1R1A protein expression, and thus results in promoting breast cancer metastasis. HOXC-AS3 could be a novel therapeutic target for breast cancer therapeutics.